2022
DOI: 10.1097/ppo.0000000000000581
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Plasma Epstein-Barr Virus DNA Load During the Follow-up Periods Predicts Recurrence and Metastasis in Nasopharyngeal Carcinoma

Abstract: BackgroundEpstein-Barr virus DNA (EBV DNA) load has been identified as a prognostic factor in nasopharyngeal carcinoma (NPC), whereas the dynamic changes in the long period have not been explored. In this study, we evaluated EBV DNA kinetics and its role in the survival.MethodsWe conducted a retrospective review of 900 NPC patients. Plasma EBV DNA levels were measured at various time points after treatment. The correlations of EBV kinetics with recurrence and metastasis were analyzed. After stratifying patient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Studies con rmed that post-treatment EBV-DNA positivity could predict early relapse and poor prognosis for patients with lymphoma [26]. Furthermore, He et al also demonstrated that elevated EBV-DNA after treatment indicated recurrence, metastasis, and unfavorable prognosis for EBV-associated nasopharyngeal carcinoma (NPC) [27]. In our study, pretreatment PEDL was compared between the TN and CP groups, we found that the median pretreatment PEDL of CP was 2.4 times higher than that of TN (P < 0.0001) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Studies con rmed that post-treatment EBV-DNA positivity could predict early relapse and poor prognosis for patients with lymphoma [26]. Furthermore, He et al also demonstrated that elevated EBV-DNA after treatment indicated recurrence, metastasis, and unfavorable prognosis for EBV-associated nasopharyngeal carcinoma (NPC) [27]. In our study, pretreatment PEDL was compared between the TN and CP groups, we found that the median pretreatment PEDL of CP was 2.4 times higher than that of TN (P < 0.0001) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Another shortcoming is that it falls short of reflecting the heterogeneity of individual tumors ( 6 ). Several studies have reported that lymph node gross tumor volume (GTVln), gross tumor volume of the nasopharynx (GTVnx), circulating CD4 T lymphocytes, lactate dehydrogenase, lactate dehydrogenase (LDH) level before treatment, hemoglobin level, and EBV DNA level were significantly associated with the distant metastases of NPC ( 6 , 39 , 40 ). Several studies have shown that the plasma EBV DNA level before treatment was related to the clinical stage and tumor burden of nasopharyngeal carcinoma, and it was currently considered to be the most important molecular marker for complementary clinical staging ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, MRI is expensive, while the phantom tumor phenomenon is not uncommon in MRI, particularly after completion of radiotherapy more than five years [ 60 ]. Recently the plasma EBV DNA has been regarded as a valuable tool for early detection of either primary surveillance or recurrence [ 61 , 62 , 63 ]. Xu et al found that the increased EBV DNA titer was present at a median of 2.6 months before radiographic progression [ 64 ].…”
Section: Discussionmentioning
confidence: 99%